European Federation of Psychologists' Associations. (Brussel : EFPA)
De European Federation of Psychologists' Associations is de overkoepelende organisatie van nationale genootschappen op het gebied van psychologie die gevestigd zijn in de Europese Economische Ruimte. // EFPA is the umbrella organization in Europe for national psychologists’ associations and currently comprises associations from 37 European countries, including all 27 member countries of the European Union.
Keywords: Psychologen; Psychologie; Psychologische tests